Pengaruh Kualitas Pelayanan Serta Citra Rasa Terhadap Kepuasan Konsumen Industri Pada PT Ranisa Rembulan Catering - Luki Irmawati; Enjang Suherman (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to identify the influence of service quality and food taste on customer satisfaction at PT Ranisa Rumble and Catering. The research method used is a quantitative approach with a survey distributed to consumers. A Likert scale questionnaire was designed to measure consumers' perceptions of various aspects of service and taste. Data analysis shows that the friendliness and professionalism of the staff, responsiveness to customer needs and requests, and efficiency in handling complaints are important factors influencing customer satisfaction. Additionally, the right combination of food and nutritional balance also play a significant role in enhancing consumer satisfaction levels. The results of this study indicate that PT Ranisa Rumble and Catering has successfully met consumer expectations through good service quality and high food taste. The conclusion of this study emphasizes the importance of continuous improvement in service aspects and menu innovation to maintain and increase customer satisfaction. These findings provide practical implications for the company in its efforts to improve the quality of services and products offered.